Effects of early-life stress and early-life enrichment on adolescent and adult behaviour in rats - Hong, Huiying (2015)
The adaptive nature of active coping has been known to enable the promotion of stress resilience and the reduction of vulnerability to neuropsychiatric disorders. But because of developmental plasticity, this ability to adapt and handle stress is largely shaped by the early-life environment. Thus, factors like the type of environmental stressors experienced and the timing of stress exposure in relation to the critical stages of development play a vital role in determining the susceptibility one has to the neuropsychiatric disorders and it becomes crucial to find out how they impact future behaviour so that we can better understand active coping abilities and use the knowledge to find ways to tackle the mental health problem. Therefore, a comparison involving the Light-Dark Box (LDB), Elevated-Plus Maze (EPM), and Aggression Test (AGT), was carried out to see how four different early-life environments, namely Maternal Separation (MS), Limited Nesting (LN), Enriched Environment (EE) and Animal Facility Rearing (AFR), affected aggression and anxiety-related behaviours in adolescent and adult rat models. Each behavioural parameter was quantified and analysed using One-way ANOVA and Fisher’s LSD test and results found that only MS displayed a significant ability to reduce anxiety and increase risk-assessment behaviour in adulthood, which is contradictory to prior literature. Hence, checks were done and the nearby construction site was found to have influenced the animals and compromised the accuracy of the results. Thus, a re-run of the study has to be done in future for verification of the results obtained.